The impact of atypical employment on individual wellbeing: evidence from a panel of British workers - Elena Bardasi; Marco Francesconi (University of Essex, Institute for Social and Economic Research (ISER), 2003)
This study explores the relationship between individual wellbeing and atypical employment, which includes both temporary and part-time employment schemes. Individual wellbeing is measured in terms of subjective indicators of mental health, general health status, life satisfaction, and job satisfaction. It addresses four questions: (1) Are workers on a temporary contract more likely to report poor health and poor life and job satisfaction than those who are employed in permanent jobs? (2) Is this the case for part-time workers compared to those who are in a full-time job? (3) Do changes in employment profiles (e.g., from a fixed-term contract to a permanent job, or from part-time employment to full-time employment) affect individuals health and life satisfaction? (4) Are there differences in such relationships between men and women? To answer these questions, logistic regression models were used to analyse a panel of almost 7000 male and female workers from the first 10 waves of the British Household Panel Study, 1991-2000. Controlling for background characteristics, atypical employment does not appear to be associated with adverse health consequences for either men or women, when both health and employment are measured at the same time. However, there is evidence that job satisfaction is reduced for seasonal/casual workers and is higher for part-timers. Taking account of selection issues does not change the general picture: the chances of ill mental and physical health and low life satisfaction are unaffected by atypical employment and some of the effects of job satisfaction persist. In addition, very few employment transitions appear to be consequential for a worsening in health outcomes, which tends to be observed in the case of job satisfaction. Although the pattern of results suggests that atypical forms of employment do not have durable adverse health consequences on workers, public policies that aim at improving the working conditions of workers in weak bargaining positions should give special attention to equity issues, including the possible health effects of experience of work in atypical employment arrangements.
Keywords: 330